Paul Rhymer radio scripts - Rhymer, Paul.
Scripts of the daytime radio comedy Vic and Sade written by Rhymer for airing on the National Broadcasting Company.
Scriptwriter and humorist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: National Broadcasting Company; Vic and Sade (Radio program); Radio comedies; Radio scripts; Authors; Humorists